Effect of Medical Thoracoscopy Guided Pleural Biopsy for Diagnosis of Moderate to Massive Exudative Pleural Effusion - Aditya Kumar Gautam; Adesh Kumar; Ashish Kumar Gupta; Somnath Bhattacharya; Prashant Yadav; Suryakant (Advanced Concepts in Medicine and Medical Research Vol. 10, 2023)
This chapter highlights about the value of medical thoracoscopic guided parietal pleural biopsy in the etiological diagnosis of exudative moderate to massive pleural effusions at a rural tertiary care centre of north India. Medical thoracoscopy has been shown to be an efficacious procedure in diagnosing unexplained exudative pleural effusions with excellent safety. Pleural biopsy under direct vision can be successfully and safely used for etiological diagnosis. This was a cross sectional study conducted in male and female patients between 18 to 70 years of age of undiagnosed and moderate to massive exudative pleural effusions. Undiagnosed pleural effusion was defined as failure to achieve a diagnosis by initial pleural fluid analysis including pleural fluid adenosine deaminase (ADA) levels <70 U/L and at least three pleural fluid analysis negative for malignant cells. The study was conducted upon 90 patients with exudative moderate to massive pleural effusion, who required intercostal drainage (ICD) for management. Exudative pleural effusions were also smear negative for acid fast bacilli (AFB) and malignant cytology. Thoracoscopic pleural specimens were diagnostic in 86 patients out of a total 90 patients (95.5%). Histopathological examination of thoracoscopic specimens revealed, Malignancy- in 31 cases (34.4%), Inflammatory 28 (31.11%), Tuberculosis in 25 patients (27.8%) and Sarcoidosis in two cases (2.22%). Four patients (4.4%) were still inconclusive on histopathology. Thus, thoracoscopic pleural biopsy is considered gold standard in diagnosis of malignant pleural effusion and tubercular pleural effusion. The safety and diagnostic yield of a medical thoracoscopic guided pleural biopsy are both good. Therefore, doctors should only use it after receiving the appropriate training.